Perubahan Fisik, Emosi, Sosial dan Moral pada Remaja Putri - Fitri Hanriyani; Esa Risi Suazini (STIKes Karsa Husada Garut, 2022)
Every teenager must experience changes, namely physical, emotional, social and moral changes. The changes that occur during adolescence, need synergy both physically, mentally socially and morally. Changes that occur may or may not be felt by every teenager. These changes are unique to be studied so that teenagers are aware of the changes in themselves so that they will be able to choose the right way of life. When they are physically aware that they are now able to reproduce, they will really take care of their healthy reproduction. When adolescents become aware of emosional, social and moral changes, adolescents will be able to refrain from deviant behavior. The purpose of this study was to determine the description of physical, emotional, social, and moral changes in young women. This research is a descriptive study using an instrument in the form of a questionnaire. Determine the sample in this study by random sampling and selected 120 respondents conducted in January 2020. The variables of this study are physical change, emotional change, social change and moral change in adolescents. The results of physical changes felt by adolescent girls: 88.33%. Changes in emotions felt by teenagers 50.5%. Social change in adolescents: 66.67%. Moral Change 90.83%. The biggest moral change they realize. Advice to adolescents after knowing the changes that occur, adolescents need to know the consequences when choosing bad behavior, so that teens will be careful in looking for identity and determine life planning in the future.